1982
DOI: 10.3168/jds.s0022-0302(82)82238-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil Ingestion by Dairy Cattle

Abstract: Sets of 5 to 10 random fecal samples were obtained from animals of various management groups of nine dairy herds. Titanium content of feces and soils to which the animals had access was determined by x-ray fluorescence spectroscopy. Titanium of feces was the indicator of soil ingestion, which was calculated for 60% digestibility of the total ration dry matter. Mean soil ingestion +/- standard error as a percent of dry matter intake by groups of lactating cows ranged from .14 +/- .02 to .53 +/- .05 for those co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
5

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 7 publications
4
40
0
5
Order By: Relevance
“…This is in accordance with previously reported values (Mayland et al, 1975;Fries et al, 1982;Thornton and Abrahams, 1983), generally classified as extreme and not relevant to current outdoor systems. Healy (1968) showed that soil intake increased with increasing stocking rate: soil intake had a yearly average of 0.5 kg/day at 1.2 cows/ha, increasing to 0.85 kg/day at 1.65 cows/ha and finally reaching 1.06 kg/day at 2.5 cows/ha, with 1.86 kg/day during the winter period.…”
Section: Soil Intake and Its Variation Factorssupporting
confidence: 93%
See 4 more Smart Citations
“…This is in accordance with previously reported values (Mayland et al, 1975;Fries et al, 1982;Thornton and Abrahams, 1983), generally classified as extreme and not relevant to current outdoor systems. Healy (1968) showed that soil intake increased with increasing stocking rate: soil intake had a yearly average of 0.5 kg/day at 1.2 cows/ha, increasing to 0.85 kg/day at 1.65 cows/ha and finally reaching 1.06 kg/day at 2.5 cows/ha, with 1.86 kg/day during the winter period.…”
Section: Soil Intake and Its Variation Factorssupporting
confidence: 93%
“…He reported that these differences were mainly because of a strong increase in soil intake over the New Zealand winter and at high stocking density. Our average and extreme values seem close to those reported in previous studies focused on extensive ranching (Mayland et al, 1975;Fries et al, 1982;Thornton and Abrahams, 1983) even if higher soil intake can be hypothesised in the case of trampling or when cows graze under heavy rainfall (Healy, 1968).…”
Section: Soil Intake and Its Variation Factorssupporting
confidence: 90%
See 3 more Smart Citations